First record of Tetranychus musae Auger, Migeon & Flechtmann, 2008 (Prostigmata: Tetranychidae) on Musa sp. (Musaceae) from Pará State, Brazil - Noronha, Aloyséia C. S.; Ferla, Noeli J.; Castro, Iury S.; Oliveira, Magali B. de; Oliveira, Izabela F. de (Entomological Communications, 2025)
This study reports the occurrence of the spider mite Tetranychus musae Auger, Migeon & Flechtmann, 2008 (Acari: Tetranychidae) on banana (Musa sp.: Musaceae) in Brazil. Specimens were collected from banana leaves grown in an intercropping system with cacao (Theobroma cacao L. - Malvaceae) at an experimental site in the municipality of Moju, Pará State. This represents the first confirmed record of T. musae in Brazil.